Analysis between Adrenal MRI Mass Size and 1 mg Dexamethasone Suppression Test in Patients with Adrenal Incidentaloma - Pinar Karakaya; Bulent Yaprak; Bahar Ozdemir; Hakan Kocoglu (Medical Laboratory Technology Journal, 2019)
This study aimed to investigate the correlation of adrenal magnetic resonance imaging (MRI) mass size and 1 mg dexamethasone suppression test results in patients with adrenal incidentaloma diagnosis. Eighty-six patients (82.6% female) with incidentally discovered adrenal masses, diagnosed and treated in the Department of Endocrinology Bakirkoy Dr. Sadi Konuk Education and Research Hospital between June and August 2017, were included in the analysis. All the patients evaluated for their hormonal functionality. 24-h urinary excretion of cortisol did not correlate with tumor size. But there was a positive correlation between longer adrenal nodule diameter and metanephrine, and there was a negative correlation between shorter adrenal nodule diameter and renin levels. We found that smaller and clinically “silent” tumors often do not demonstrate subclinical hormonal activity.